2010
DOI: 10.1097/jgp.0b013e3181ab8b62
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Cognitive Activity Compensates for Education Differences in Episodic Memory

Abstract: Objectives: To test the hypothesis that frequent participation in cognitive activities can moderate the effects of limited education on cognitive functioning. Design:A national study of adult development and aging, Midlife in the United States (MIDUS), with assessments conducted at the second wave of measurement in 2004-2006. Setting: Assessments were made over the telephone (cognitive measures) and in a mail questionnaire (demographic variables, measures of cognitive and physical activity, and self-rated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
165
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(190 citation statements)
references
References 37 publications
20
165
1
2
Order By: Relevance
“…In line with prior research, 12,34,35 two factors were assessed, episodic memory and executive functioning. They were computed on the basis of seven cognitive dimensions measured by the Brief Test of Adult Cognition by Telephone (BTACT).…”
Section: Outcome Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with prior research, 12,34,35 two factors were assessed, episodic memory and executive functioning. They were computed on the basis of seven cognitive dimensions measured by the Brief Test of Adult Cognition by Telephone (BTACT).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…12,34,35 This included two measures of episodic memory (immediate and delayed free recall of 15 words), working memory span (backward digit span-the highest span achieved in repeating strings of digits in reverse order), verbal fluency (the number of words produced from the category of animals in 60 seconds), inductive reasoning (completing a pattern in a series of five numbers), processing speed (the number of digits produced by counting backward from 100 in 30 seconds), and attention switching and inhibitory control (the Stop and Go Switch Task). 34,35 Following exploratory and confirmatory factor analysis, 12 two cognitive factors were computedepisodic memory (immediate and delayed word recall) and executive functioning (all other measures), by averaging the variables loading on each factor and standardizing to z scores. 12 A prior validation study revealed the equivalence of phone testing and faceto-face testing for the BTACT, and shows that the tests used have acceptable psychometric properties in samples who vary widely in age, education, and socioeconomic background.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning activity engagement, we expected, based on previous research findings (Hertzog 2009;Hertzog et al 2008), positive associations between cognitively demanding out-of-home activities and episodic memory (Lachman et al 2010), as well as between physically demanding activities, executive functions (Colcombe and Kramer 2003;Allmer 2005;Cotman and Berchtold 2002;Eggermont et al 2009) and working memory (Sibley and Beilock 2007).…”
Section: Hypothesesmentioning
confidence: 99%
“…Tal achado é corroborado pela literatura, em que, segundo alguns autores, a educação desempenha papel fundamental para uma memória bem-sucedida no envelhecimento. [32][33][34] Zahodne et al 32 descreveram um melhor desempenho em memória episódica de idosos com alta escolaridade, comparada com idosos de baixa escolaridade e mesma idade. No entanto, o declínio observado na memória episódica ao longo dos anos foi semelhante em ambos os grupos, sugerindo que a escolaridade pouco influencia no curso da memória no processo de envelhecimento.…”
Section: Todos Os Questionáriosunclassified